Design and fabrication of the passive solar still using blue metal stone. Issue 2 (17th February 2017) - Nithyanandam, C.; Baskar, G.; Mohanty, Nalin Kant
Abstract : In this paper, an attempt has been made to find out the effect of blue metal stone on heat transfer coefficient for a passive single-slope distillation system in summer climatic conditions. The experiments have been conducted on a south facing, single slope, solar still of 10° inclination of condensing cover, in summer climatic conditions for 24 h on 5 different days for three different sizes of blue metal stone from 6 to 20 mm and this is finally compared by using the basin without any absorbing material. The thermal efficiency is calculated by using the energy balance equation.